ANALISIS KESIAPAN PENERAPAN SAK-EMKM UNTUK PELAPORAN KEUANGAN UMKM PADA UMKM DI KABUPATEN BANYUMAS - Tjahjani Murdijaningsih; Tunggul Priyatama (Majalah Imiah Manajemen & Bisnis, 2019)
This research is entitled "Analysis of the Readiness of SAK EMKM Application for MSME Financial Reporting at UMKM in Banyumas ". This study aims to determine the factors that influence the readiness of implementing SAK EMKM as a new standard that is more representative of EMKM on financial reports. The population in this study were UMKM actors in the Banyumas. The results showed that motivation did not have a significant effect on the application of SAK EMKM, while socialization had a significant effect on the application of SAK EMKM, and perceived ease of use had a significant effect on the application of SAK EMKM in Banyumas, this indicated that the better the socialization and perceived convenience of SAK EMKM, the better There is also good desire of UMKM actors to implement SAK EMKM, while motivation does not play a role in implementing SAK EMKM